The role of elastography in determining the risk of malignant thyroid nodules in children - Kiszka-Wiłkojć, Aleksandra; Taczanowska-Niemczuk, Anna; Januś, Dominika; Maślanka, Marcin; Godlewska, Joanna; Kujdowicz, Monika; Wiłkojć, Michał; Górecki, Wojciech (Frontiers in Endocrinology, 2024)
Introduction: Ultrasonography is fundamental method of diagnosing focal thyroid lesions. The additional element of ultrasound examination is Strain Elastography which allows for determining the degree of elasticity of the nodule while comparing it to the surrounding thyroid parenchyma. Pediatric thyroid nodules have a higher malignancy risk than in adults, warranting the consideration of fine-needle aspiration biopsy (FNAB) in children. Material and Methods: A prospective data analysis of children with focal thyroid lesions treated from 2021 to 2022 was performed. The patients underwent ultrasound and elastography examinations to obtain the Strain Ratio (SR) of the nodules and were qualified for FNAB. SR was determined by the windowing method of relative strains in a semi-quantitative assessment. The FNAB score was determined on the Bethesda scale and the histological examination of the thyroid nodule was performed. The SR values were stratified in three groups: I - thyroid cancer, II - low-risk thyroid tumors, and III - benign lesion. The Kruskal-Wallis test was used to find the relation between the value of SR elastography and the malignancy, with the p value < 0.05 considered significant. The data were analyzed using the multiple comparisons test. Results: The 123 FNABs were performed in 100 patients. The final analysis included 119 nodules in 96 patients. In 19 cases, the nodule was malignant, in 5 cases they were low-risk tumors, and in 95 - benign lesions. A difference of the SR value between groups in the pairs of malignant and benign tumors, and malignant and low-risk tumors was revealed. Since no statistically significant difference in the level of elastography was found between benign and low-risk tumors, both groups were combined and formed a group of benign tumors. For the combined groups, the Man-Whitney test was performed, confirming that there was a statistically significant difference between the groups of malignant and benign tumors in the value of SR elastography. The cut-off point for SR for malignant tumors was >3. Conclusions: The SR index of elastography is significantly higher in malignant nodules. and might be used to select changes with an increased risk of malignancy in thyroid ultrasound of children.